Literature Review: Analysis of Factors Associated with the Incidence of Pneumonia in Toddlers (Age > 12-59 Months) - Irmae Irmae; Edi Hartoyo; Meitria Syahadatina Noor; Mohamad Isa; Roselina Panghiyangani (GLOBAL HEALTH SCIENCE GROUP, 2026)
Pneumonia is a major cause of infant mortality in Indonesia. Pneumonia is influenced by intrinsic and extrinsic factors, such as immunization status, exclusive breastfeeding, nutritional status, home environment, and family socioeconomic status. Objective to analyze factors associated with the incidence of pneumonia in toddlers (aged > 12-59 months) through a literature review. Literature review of national journals published between 2021 and 2025. Databases from Google Scholar and PubMed with keywords